Safety of balanced propofol and midazolam in upper gastrointestinal endoscopy for sedation in cirrhotic patients - Laima Alam; Mohammad Asif Khattak; Mafaza Alam (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: Sedation for upper gastrointestinal endoscopy (UGIE) in patients with cirrhosis is theoretically associated with high incidence of adverse events due to low levels of binding proteins and decreased hepatic clearance of drugs. The objective of the study was to assess the safety of combined propofol and midazolam sedation in cirrhotic patients undergoing UGIE. Methods: A total of 500 patients undergoing UGIE were divided in to two groups in a prospective observational study from Jan 1st 2018 to June 30th 2018. Group (I) consisted of cirrhotic patients who underwent the procedure with sedation and Group (II) consisted of non-cirrhotic patients who opted for sedation. The main outcome measurements included vitals monitoring before, during and after procedure, total sedation dose, time to initial and deep sedation, recovery time and complications. Results: There was no significant difference between sedation safety and rate of complications for the cirrhotic and non-cirrhotic patients except for the recovery period during initial 10 minutes. The Modified Aldrete score for the cirrhotic patients was 9.5±0.5 min as compared to 9.8±0.4 min for non-cirrhotic patients (p<0.001) at 10 minutes. Grade 2 hepatic encephalopathy was seen in 0.8% of the cirrhotic patients who required hospitalization for 24 hours. Also balanced sedation was acceptable by the patients and the endoscopists equally with statistically significant scores on endoscopist’s assessment of co-operation and assessment of patient’s satisfaction scores. Continuous...